A PRELIMINARY STUDY OF THE SUMMER ASPECT OF WEEVIL (COLEOPTERA: CURCULIONOIDEA) FAUNA OF THE OVČAR-KABLAR GORGE (WESTERN SERBIA) (Acta Entomologica Serbica, 2019)
The first preliminary overview of the weevil (Colеoptera: Curculionoidea) fauna registered in the Ovčar-Kablar Gorge (western Serbia) is given. The field research was conducted in June and July 2016 at seven localities. Among a total of 62 identified species and 7 subspecies, 14 are recorded for the first time for the Republic of Serbia, including one Balkan endemic species (Cleopomiarus medius). One of the registered species (Sciaphobus caesius) is protected by the national regulations of the Republic of Serbia.